Connecting for Innovation: Four Universities Collaboratively Preparing Pre-service Teachers to Teach in Rural and Remote Western Australia - Sue Trinidad; Elaine Sharplin; Sue Ledger; Tania Broadley (Journal of Research in Rural Education, 2014)
In 2010 a group of teacher educators from four universities, experienced in rural and remote education, formed the Tertiary Educators Rural, Regional and Remote Network (TERRR Network). The collaborative goal was to improve the quality of graduates taking appointments beyond the metropolitan areas of Western Australia. The TERRR Network developed a research project to improve the capacity of universities to prepare teachers for employment in rural and remote locations. A range of outcomes emerged from the project, including: 1) the development of seven rural and remote-oriented curricula modules linked to the Australian Professional Standards for Teachers; 2) a cross-institutional fi eld experience, and; 3) the development of a community of practice involving the Department of Education, universities and schools to address the logistical implications of placing pre-service students in rural and remote locations. This paper reports on the fi ve phases of the project design, with a focus on learning in the fi eld and concludes with refl ections on the collaborative process used by the four universities in order to ensure that research evidence informs future policy and program development.